Analysis of Value Addition of Cassava Products in Nasarawa State, Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
The study examined cassava products value addition in Nasarawa state, Nigeria. Data were collected from 1,360 respondents and analysed using general linear model statistics. The result showed that boiled cassava root, cassava bread, cassava chips, cassava flakes, garri, High Quality Cassava Flour (HQCF) and meat pie had mean incomes of N555.00, N3,429.17, N225.00, 642.86, N3,642.86, N119.00, 127.66, N121, 288.37 and N1,490.00, respectively. The mean incomes from cassava chips, HQCF, and garri were significantly (p
Keywords: Cassava; Differentials; Income; Processors; Products; Value